Influence of upper-body high-intensity intermittent training on energy metabolism and maximal oxygen uptake in elite swimmers - Zhang, Lei; Li, Hanyi; Wang, Tongling; Chen, Chao (Frontiers in Physiology, 2025)
PurposeThis paper aimed to investigate the effects of upper-body high-intensity interval training (HIIT) on energy metabolism and maximal oxygen uptake (VO2max) in elite swimmers.MethodsA randomized controlled trial was conducted, in which elite swimmers were stratified and randomly assigned to either an upper-body HIIT group or an upper-body moderate-intensity continuous training (MICT) group. The HIIT group performed upper-body HIIT sessions lasting 60 min, including a warm-up, main workout, and cool-down at a 2:3:1 time ratio. The main workout consisted of circuit-based HIIT involving eight exercises, each performed for 20 s with 10 s of rest, totaling 230 s per circuit, with 3-min interset intervals, repeated for three sets. The MICT group followed a similar session structure except that the main workout involved eight continuous exercises performed for 60 s each with 20-s rest intervals and 20-s interset intervals and also repeated for three sets. Pre- and post-intervention assessments included upper-body cycle ergometry to evaluate the VO2max and indices of energy metabolism. Repeated-measure ANOVA was used to analyze changes in VO2max and energy metabolism indicators.ResultsPrior to the intervention, no significant differences in VO2max or energy metabolism indices between the two groups were noted. After 4 weeks of training, the HIIT group exhibited significant improvements in VO2max and energy metabolism parameters as assessed by upper-body ergometry (p < 0.05). By contrast, the MICT group showed no significant changes in these indicators (p > 0.05). A significant interaction effect was observed between time and group (p < 0.05).ConclusionA 4-week program of upper-body HIIT significantly enhances energy metabolism and VO2max in elite swimmers. These findings provide a theoretical basis for incorporating upper-body HIIT into the training regimens of competitive swimmers to optimize aerobic capacity and metabolic efficiency.